How Business Income Measures Affect Income Inequality and the Tax Burden - Rolf Aaberge; Marco Francesconi; Jørgen Modalsli; Ola L. Vestad (CESifo GmbH, 2024)
This paper presents estimates of income concentration and inequality for Norway using a new comprehensive measure of income, which identifies business income as it is earned by companies rather than when it is paid out as dividends to owners. We assemble several sources of high quality register data that allow us to account for multiple layers of business ownership across all companies between 2001 and 2018. Compared to official statistics, the new measure implies that the share of income attributable to the top 1% of the distribution more than doubles and the Gini coefficient estimates increase by about 40%. Our new measure identifies substantial tax regressivity for individuals in the top percentile, a feature that cannot be detected by standard income measures. For instance, while the share of gross income paid in taxes by individuals at the 99th percentile is about 36% in 2016, the corresponding share paid by individuals in the top 1% is 19%.
Keywords: D31; D63; E01; H24; 330; income distribution; top income shares; Gini coefficient; dividends; retained earnings; tax burden